2007
DOI: 10.1007/978-3-540-72731-6_33
|View full text |Cite
|
Sign up to set email alerts
|

A New Algorithm for the Distributed RWA Problem in WDM Networks Using Ant Colony Optimization

Abstract: Abstract. We present a new algorithm based on ant colony optimization to solve the dynamic routing and wavelength assignment problem in a distributed manner. The algorithm uses the ant colony optimization metaheuristic to obtain updated information about the network state, which is then used to find the routes and wavelengths to establish new connections through an adaptive process able to deal with dynamic changes in network state. By means of simulation we show that the algorithm leads to lower blocking prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…(This effect of reduction of the blocking probability due to outdated databases when increasing the load by augmenting the duration of the connections has also been reported in other works on distributed lightpath establishment, e.g. [21,22]). Fig.…”
Section: Advantages Of Using Etm In An On-demand Lightpath Establishmsupporting
confidence: 70%
“…(This effect of reduction of the blocking probability due to outdated databases when increasing the load by augmenting the duration of the connections has also been reported in other works on distributed lightpath establishment, e.g. [21,22]). Fig.…”
Section: Advantages Of Using Etm In An On-demand Lightpath Establishmsupporting
confidence: 70%
“…Aragon et al also used ACO to solve the RWA problem in WDM networks. They have shown that ACO outperforms other distributed routing algorithms applied in WDM networks.…”
Section: Routing Algorithms For Optical Burst Switched Networkmentioning
confidence: 99%